Adrenalectomy does not improve survival rates of patients with solitary adrenal metastasis from non-small cell lung cancer - Huang S; Kong Q; Chen X; He J; Qin J; Chen Z (Dove Medical Press, 2017)
Shao-Hong Huang,1,* Qing-Lei Kong,2,* Xue-Xia Chen,3 Jin-Yuan He,1 Jie Qin,4 Zhuang-Gui Chen5,6 1Department of Cardiothoracic Surgery, The Third Affiliated Hospital, Sun Yat-sen University, Guangzhou, China; 2Department of Emergency, the Third Affiliated Hospital, Sun Yat-sen University, Guangzhou, China; 3Department of Nursing, Eastern Hospital of The First Affiliated Hospital, Sun Yat-sen University, Guangzhou, China; 4Department of Radiology, The Third Affiliated Hospital, Sun Yat-sen University, Guangzhou, China; 5Department of Pediatrics, Pediatric Intensive Care Unit, The Third Affiliated Hospital of Sun Yat-sen University, 6Institution of Respiratory Disease of Sun Yat-sen University, Guangzhou, China *These authors contributed equally to this work Background and purpose: Several case reports and studies have suggested that there is an increased survival rate for patients who undergo resection of solitary adrenal metastasis from non-small cell lung cancer (NSCLC). This study aimed to investigate whether NSCLC patients with solitary adrenal metastasis could gain a higher survival rate after adrenalectomy (ADX) when compared with those patients undergoing nonsurgical treatment, and to investigate the potential prognostic factors.Patients and methods: A total of 1,302 NSCLC inpatients’ data from 2001 to 2015 were retrospectively reviewed to identify those with solitary adrenal metastasis. Overall survival for those who underwent both primary resection and ADX was compared to those patients with conservative treatment using the log-rank test. Potential prognostic variables were evaluated with univariate and multivariate analyses including clinical, therapeutic, pathologic, primary and metastatic data.Results: A total of 22 NSCLC patients with solitary adrenal metastasis were identified, with an overall median survival of 11 months (95% confidence interval: 9.4–12.6 months) and a 1-year survival rate of 51.4% (95% confidence interval: 29.6%–73.2%). All of the patients had died by 30 months. There was no significant survival difference between patients who underwent primary and metastasis resection (n=10) and those treated conservatively (n=12), (P=0.209). Univariate analysis identified Eastern Cooperative Oncology Group performance status (ECOG PS) as the significant predictor of survival (P=0.024). Age (<65 vs ≥65 years), sex, pathologic type, mediastinal lymph node stage (N2 vs N0/N1), primary tumor size (<5 vs ≥5 cm), primary location (central vs peripheral), metastatic tumor size (<5 vs ≥5 cm), metastasis laterality, synchronous metastasis, and metastatic field radiotherapy were not identified as potential prognostic factors in relation to survival rate. In multivariate analysis, a stepwise selection procedure allowed both ECOG PS (P=0.007, relative risk =3.57) and pathologic type (P=0.069) to enter the Cox’s hazard function.Conclusion: Primary and metastatic radical resection may not prolong the survival of NSCLC patients with solitary adrenal metastasis. ECOG PS and pathologic type might be the prognostic factors for these patients. Keywords: adrenalectomy, solitary metastasis, non-small cell lung cancer, survival, prognostic factors